Impact of State Sentencing Policies on Incarceration Rates in the United States, 1975-2002 - Stemen, Don ([Verlag nicht ermittelbar], 2007)
In order to assess the impacts of state-level sentencing and corrections policies in the United States implemented between 1975 and 2002 on state incarceration rates during that same time period, researchers conducted a two-phase study between November 2002 and March 2004. The first phase of the research involved building a framework for understanding the types of state-level sentencing and corrections policies in use between 1975 and 2002. Phase two of the project consisted of state-level data collection for all 50 states for all study years, 1975 to 2002. The researchers produced a dataset containing outcome variables that focus on the change and growth in state incarceration rates, non-policy control variables that were found in previous studies to be associated with changes in incarceration rates, and policy variables regarding sentencing structure, drug policy, time served requirements, habitual offender laws (HOL), and mandatory sentences.